Two new species of the genus Austrohancockia Günther, 1938 (Orthoptera: Tetrigidae, Cladonotinae) from China, with a key to the species of the genus. (3rd July 2019) - Deng, Wei-An; Lei, Chao-Liang
ABSTRACT: The taxonomy of the tetrigid genus Austrohancockia Günther is reviewed. Two new species, Austrohancockia albitubercula Deng, sp. nov. and A . latifemora Deng, sp. nov., are described from China. An updated identification key to all known species in the genus is given. http://www.zoobank.org/urn:lsid:zoobank.org:pub:84295200-5043-471A-9332-8EA2F30F62C6